ANALISIS DASAR PERTIMBANGAN HAKIM MENETAPKAN BESARAN NAFKAH IDDAH, MAḌIYAH DAN MUT’AH, PADA CERAI TALAK DI PENGADILAN AGAMA KABUPATEN KEDIRI (STUDI KASUS PERKARA PUTUSAN NOMOR:852/PDT.G/2022/PA.KAB.KDR) (AL MUNAZHZHARAH, 2025)
Divorce is a legal event in the form of breaking the marital bond between husband and wife, with legal reasons and through a certain legal process that must be stated strictly before the court. Judge consideration is one of the most important aspects in deciding the realization of the value of a judge who contains justice and contains legal certainty, besides that it also contains benefits for the parties concerned so that the judge's consideration must be thorough, good and fast. Considerations of Juridical Judges Juridical considerations are the judge's considerations which are based on the factors revealed in the trial and by law have been stipulated as things that must be included in the decision. This type of research uses empirical legal research, the research approach uses a legal sociology approach, research data uses primary and secondary data. Based on the procedures for examining  cases  of  divorce  decisions  with  iddah,  mut'ah  and  madiyah  maintenance  Decision  Number : 852/Pdt.G/2022/PA.Kab.Kdr, must go through various stages of Examination, Reconventional Examination, Mediation, Trial, Conduct Replica and Duplik, Trial of Proof of Plaintiff and Defendant, Trial of Conclusions, Readout of Verdict. Basic analysis of Judges' Considerations in determining the amount of living for iddah, madiyah and mut'ah Decision Number: 852/Pdt.G/2022/PA.Kab.Kdr concluded that the Judge's Considerations in  determining  the  amount  of  living  are  using  Juridical  and  Non-Juridical  Considerations.  Juridical considerations include: Article 149 letter (a) and Article 158 letter (b) KHI, Law Number 1 of 1974, Article 80 Paragraph 2 KHI and considerations of non-juridical judges covering the consequences of the actions of the respondent, condition and role or position of the respondent.